2017
DOI: 10.1111/febs.14162
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β1‐induced CK17 enhances cancer stem cell‐like properties rather than EMT in promoting cervical cancer metastasis via the ERK1/2‐MZF1 signaling pathway

Abstract: Tumor metastasis remains a major obstacle for improving overall cancer survival in cervical cancer (CC), which may be due to the existence of tumor microenvironment-related cancer stem cells (CSCs) and epithelial-mesenchymal transition (EMT). The mechanism underlying these processes needs to be further elucidated. Here, we report that TGF-β1, one of the key microenvironmental stimuli, can enhance CSC characteristics, facilitate the EMT, and induce CK17. Silencing CK17 expression attenuated CSC-like properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 49 publications
1
46
0
Order By: Relevance
“…105 Findings in a cervical cancer study showed that TGF-β1 promoted EMT in cancer cells and helped them to obtain a CSC phenotype. 80 Similarly, in hepatocellular carcinoma, TGF-β1 could achieve the same effect as in cervical cancer by downregulating TP53INP1 through miR-155. 78 These studies suggest that the radiation-induced TGF-β signalling pathway plays an important role in EMT and obtaining a CSC phenotype, thereby promoting tumour metastasis.…”
Section: Csc-associated Epithelial-mesenchymal Transitionmentioning
confidence: 98%
See 2 more Smart Citations
“…105 Findings in a cervical cancer study showed that TGF-β1 promoted EMT in cancer cells and helped them to obtain a CSC phenotype. 80 Similarly, in hepatocellular carcinoma, TGF-β1 could achieve the same effect as in cervical cancer by downregulating TP53INP1 through miR-155. 78 These studies suggest that the radiation-induced TGF-β signalling pathway plays an important role in EMT and obtaining a CSC phenotype, thereby promoting tumour metastasis.…”
Section: Csc-associated Epithelial-mesenchymal Transitionmentioning
confidence: 98%
“…In addition, it has been confirmed by evidence that CSCs have mesenchymal phenotypes, suggesting their high capacity for migration and invasion. [78][79][80] IR can induce non-CSCs to have stronger migration activity, which is closely related to the acquisition of the CSC phenotype and radiation-induced epithelial-mesenchymal transformation (EMT), 58 which is associated with relapse and metastasis.…”
Section: Csc-associated Relapse and Metastasis In Oral Cancer Post-ramentioning
confidence: 99%
See 1 more Smart Citation
“…The association between 1,25 (OH) 2 D 3 and TGF-β/Smad signaling pathway 28,29 led us to consider whether TGF-β/Smad signaling pathway induces the IRX4-induced cancer stem cell-like properties. Studies have shown that TGF-β1 signaling promotes cancer cell stemness, leading to tumor metastasis 30,31 . Whether TGF-β1 increased cancer cell stemness by regulating IRX4 and how to regulate TGF-β1 signaling mediated cancer stem-like properties is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Keratinocyte differentiation, skin development and epidermis development gene sets enriched in the high PPS20 group include many genes belonging to the keratin family, among which KRT16 has been used as a basal cell marker [28,29]; KRT17 has been shown to induce cancer stem cell-like properties in cervical cancer [30] and tumor growth, motility and invasion in gastric cancer [31], which is also associated with poor prognosis in breast cancer [32]. Formation of primary germ layer and endoderm gene sets were also enriched in tumors with high PPS20.…”
Section: Molecular Characteristics Of Pps20-identified Pdac Sub-groupsmentioning
confidence: 99%